INVESTIGATING TEACHERS ATTITUDES TOWARDS USING VISUAL AIDS IN DEVELOPING VOCABULARY - Mohummed, Hayfa Kadhim; Yaseen, Inas Kamal (PEOPLE: International Journal of Social Sciences, 2017)
Vocabulary is one element in English learning, particularly at low level of communicating meanings. This study aims to identify and classify teachers attitudes towards Using visual Aids on developing vocabulary. The study is restricted to The teachers (females) of the primary schools in Missan during the academic year 2015-2016.The sample of this study includes 35 fourth and fifth year teachers 'primary schools of the English language in Misan Governorate. A questionnaire, has been constructed to be the main instrument used. According to the findings of this study, the researcher considered the weighted mean 50% and 68% as an item that gain low positive attitude from teachers. Consequently, Three items were gaining high attitude from teachers.